Effect of Microstructure on the Thermal Expansion Coefficient of Sintered Cordierite Prepared from Sol Mixtures. Issue 6 (26th April 2013) - Kobayashi, Yuichi; Katayama, Masaki; Kato, Makiko; Kuramochi, Shingo; Parthasarathy, T.
<x xml:space="preserve">Abstract</x> Dense cordierite ceramics were prepared from a sol mixture of alumina, silica, and magnesia, and the relationship between microstructure and thermal expansion was clarified for sinters with relative density greater than 97%. In the dense cordierite ceramics, submicrometer‐sized primary cordierite crystals aligned in the same crystal orientation and constituted the domain structure. We discovered that these domain structures could be easily observed by optical polarizing microscopy and quantified by digital image analysis of the photographs. The occurrence of microcracks between domains larger than 40 μm was induced by the thermal expansion anisotropy of the cordierite crystal axes. As a result, the mean thermal expansion coefficient of the cordierite ceramics decreased to 0.4 × 10−6 K−1 from the average value of the crystal axes of 1.7 × 10−6 K−1. This lower thermal expansion coefficient could be theoretically explained by partial microcracking.